Evaluasi Fungsi Purchasing Dalam Proses Pengadaan Barang Di Swiss-Bel Hotel Pondok Indah (Jurnal Ilmiah Pariwisata, 2016)
Hotels often referred to as a 'home away from home'. A place where tourists stop being a traveler and being a guest. A hotel typically offers a range of accommodation and services, which may include a suite, common dining and lounge facilities banquet facilities, and entertainment facilities. The main characteristic feature that sets the hotel apart from other types of accommodation are complete facilities and services available. In addition to the availability of public services, a variety of other services such as airline tickets, tours, reservation booking, and others. The hotel size ranges from twenty to more than two thousand rooms. hotels found in the city center, suburban and airport locations.Purchasing Department is the center point of the transaction or purchase of any kind of goods for hotel operations, so that the purchasing department is often described as the central purchasing company or hotel in question. The task of purchasing at Swiss-Bel Hotel Pondok Indah is in conformity with the task of purchasing the authors noted in the theoretical basis. The purchasing department function is to plan and coordinate the process of making the PR and PO for the needs of all departments in the hotel. With the PR and PO and coordination between departments is good, then the procurement process at the hotel can run smoothly.This type of research is qualitative descriptive research that is done through case studies, interviews, and direct observation of The Role of Purchasing at the hotel.